Analisis Persamaan pada Pokoknya Atas Nomenklatur Alfanumerik dan Implikasi Prosedural Putusan Niet Ontvankelijke Verklaard dalam Sengketa Merek Otomotif - Fitri Maharani Putri Wiratama (CV. ITTC INDONESIA, 2026)
The increasing use of alphanumeric designations in the automotive industry has raised legal challenges concerning trademark protection, particularly in determining substantial similarity between registered and subsequently used marks. This study examines the legal parameters for assessing substantial similarity in alphanumeric trademarks and analyzes the procedural implications of the Niet Ontvankelijke Verklaard decision in the dispute between Bayerische Motoren Werke Aktiengesellschaft (BMW AG) and PT BYD Motor Indonesia regarding the designation “M6”. The research aims to determine whether the use of “BYD M6” constitutes substantial similarity with BMW AG’s registered trademark “M6” and to evaluate the legal consequences arising from a judicial decision that does not examine the merits of the dispute. This study employs normative legal research using statutory, conceptual, and case approaches. Primary legal materials consist of Law Number 20 of 2016 concerning Trademarks and Geographical Indications and Decision Number 19/Pdt.Sus-HKI/Merek/2025/PN Niaga Jkt.Pst. The findings reveal that the designation “M6” fulfills the criteria of substantial similarity based on visual, phonetic, conceptual, and likelihood of confusion analyses. The addition of the corporate identifier “BYD” does not eliminate the dominant character of the designation “M6” as a product identifier. The study further finds that the Niet Ontvankelijke Verklaard decision does not resolve the substantive trademark dispute but creates procedural consequences that postpone legal certainty and delay the enforcement of trademark rights. This research contributes to the development of legal standards for assessing alphanumeric trademarks and highlights the need for clearer guidelines in resolving automotive trademark disputes in Indonesia.